Giant colonic volvulus due to colonic pseudo-obstruction. (25th February 2015) - Karaman, Kerem; Tanoglu, Alpaslan; Beyazit, Yavuz; Han, Ismet
Abstract : Acute colonic pseudo-obstruction (ACPO), also known as Ogilvie's syndrome, is a clinical syndrome characterised by gross dilation of the caecum and right hemicolon, which sometimes extends to the sigmoid colon and rectum in the absence of an anatomic lesion in the intestinal lumen. It is characterised by impaired propulsion of contents of the gastrointestinal tract, which results in a clinical picture of intestinal obstruction. A careful examination of the markedly distended colon can exclude several colonic pathologies, including mechanical obstruction and other causes of toxic megacolon. ACPO can sometimes predispose or mimic colonic volvulus, especially in geriatric patients.